If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11t + -16 = 32 + -1t Reorder the terms: -16 + 11t = 32 + -1t Solving -16 + 11t = 32 + -1t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add 't' to each side of the equation. -16 + 11t + t = 32 + -1t + t Combine like terms: 11t + t = 12t -16 + 12t = 32 + -1t + t Combine like terms: -1t + t = 0 -16 + 12t = 32 + 0 -16 + 12t = 32 Add '16' to each side of the equation. -16 + 16 + 12t = 32 + 16 Combine like terms: -16 + 16 = 0 0 + 12t = 32 + 16 12t = 32 + 16 Combine like terms: 32 + 16 = 48 12t = 48 Divide each side by '12'. t = 4 Simplifying t = 4
| 58=x+23 | | 3b^3-15b^2=108b | | -7w^2+6w-7=0 | | ln(3-x)+ln(-2-x)=ln(2-8x) | | X+1=35 | | -2w^2-7w+4=0 | | x^3-4x=-(x+2) | | 2/5x+1/5=35 | | 5x+3y=460 | | 315+600+532+220+246+567+274+105= | | 2(b+2)-(8+b)=-6 | | 7(0)+11y=4 | | 6p+9=15+5p | | x^3-5x^2+2=0 | | (x^-2y^2)2/x^4y^8 | | 3(0)-13=y | | (3.14)(78.50)(9)= | | z^2/6-7/2-45=0 | | ((8t^2-35t+12)/(8t^2+61t-24))/((32t^2-36t+9)/(4t^2+29t-24)) | | x+5(7)=15 | | 3.14*78.50*9= | | 832=(12+2x)(18+2x) | | 14X^7/21X^4 | | 0.6x+1.2=0.8x-0.2 | | 101/4x1.5 | | 1/3(-3)=y | | 5x-9=5x+1 | | 1/3x-3=y | | (2x/x^2-8)=-2/7 | | 2000=(20+2x)(30+2x) | | -y+7=-9 | | 5-2x=79 |